(untitled) (Law, State and Telecommunications Review, 2014)
Purpose ”“ This paper aims to analyze the relationship between the concept of Regulatory State and democracy through the lenses of the cyber warfare. This activity, which disregards borders and does not even respect the declaration of war, can often ensure basic rights without which the law could not. Methodology/approach/design ”“ The research was implemented using descriptive and logical-intuitive approach, exploring how the cyber warfare is structured in Brazil and verifying its conformation with a legally proper model. Findings ”“ It has been found that this is a topic scarcely explored by national doctrine and judicial decisions, although cyber war is a recurrent subject in society nowadays. Its connection with national security and fundamental rights increases the importance of approaching the subject. An adequate regulation could increase the results of the cyber warfare once it provides legal certainty for professionals, while ensuring constitutional rights. Practical implications ”“ This paper may help in the discussion of the regulation of cyber ”‹”‹warfare, guiding researchers to controversial aspects, the regulation of which offers convenience for society and for professionals working in this field. Originality/value ”“ It is expected that this paper foments socio-legal debate on relevant topics concerning cyber warfare, by identifying potential problems. It might prevent, in practice, future legal conflicts and increase the perception of security when using computer networks.